APOINTING A DATABASE TO THE GC-2014 GAS CHROMATOGRAPH - Seif Eddine, MEFTAH (University Of El Oued, 2012)
اﻟﻤﻠﺨﺺ GC ) ﻧﻌﻠﻢ ان اﻟﻜﺮوﻣﺎﺗﻮﻏﺮاﻓﯿﺔ اﻟﻐﺎزﯾﺔ اﻟﻤﺰودة ﺑﻜﺎﺷﻒ اﻟﺘﺄﯾﻦ ﺑﺎﻟﻠﮭﺐ -( ﻟﮭﺎ ﻗﺪرة ﻋﻠﻰ اﻟﺘﺤﻠﯿﻞ FID اﻣﺎ اﻟﻜﺮوﻣﺎﺗﻮﻏﺮاﻓﯿﺔ اﻟﻐﺎزﯾﺔ اﻟﻤﺰودة ﺑﻜﺎﺷﻒ ﻣﻄﯿﺎﻓﯿﺔ اﻟﻜﺘﻠﺔ ، اﻟﻜﻤﻲ اﻟﻌﺎﻟﯿﺔ ﺟﺪا ﻟﮭﺎ ﻗﺪرة ﻋﻠﻰ (GC-MS) اﻟﺘﺤﻠﯿﻞ اﻟﻜﯿﻔﻲ. ﻓﻲ ھﺬا اﻟﻌﻤﻞ ﻗﻤــــﻨﺎ ﺑﻤﺤﺎوﻟﺔ ﺗﺰوﯾﺪ اﻟﻜﺮوﻣــﺎﺗﻮﻏﺮاﻓﯿﺔ اﻟﻐﺎزﯾﺔ اﻟﻤﺰودة ﺑﻜﺎﺷﻒ اﻟﺘﺄﯾﻦ ﺑﺎﻟﻠﮭﺐ )GC -( ﺑﻘﺎﻋﺪة ﺑﯿﺎﻧﺎت و ذﻟﻚ ﻟﻜﻲ ﺗﻜﻮن ﻟﮭﺎ ﻗﺪرة ﻋﻠﻰ اﻟﺘﺤﻠﯿﻞ اﻟﻜﻤﻲ و اﻟﻜﯿﻔﻲ ﻣﻌﺎ. FID ﺗﻢ اﺳﺘﺨﺪام ﻣﺰﯾﺞ ﻣﻦ اﻟﻤﺮﻛﺒﺎت اﻟﻄﯿﺎرة ﺑﻌﺪﯾﺪ ﻣﻦ اﻟﺴﺮﻋﺎت اﻟﺘﺪﻓﻖ اﻟﺨﻄﯿﺔ ﻟﻠﻐﺎز اﻟﺤﺎﻣﻞ و ﻓﻲ (N2) و درﺟﺔ ﺣﺮارة ﻣﺒﺮﻣﺠﺔ ﻟﻠﻌﻤﻮد ، درﺟﺔ ﺣﺮارة ﺛﺎﺑﺘﺔ ﻗﺼﺪ اﺧﺘﯿﺎر اﻟﺸﺮوط اﻟﻤﻨﺎﺳﺒﺔ اﻟﺘﻲ ﺗﻌﻄﯿﻨﺎ (DB-5) اﺣﺴﻦ ﻓﺼﻞ ﻟﻠﻤﺮﻛﺒﺎت ﻓﻲ اﻟﻤﺰﯾﺞ. C ﺛﻢ ﺗﻢ ﺣﻘﻦ ﺧﻠﯿﻂ ﻣﻦ اﻷﻟﻜﺎﻧﺎت اﻟﻨﻈﺎﻣﯿﺔ إﻟﻰ 14 ﻓﻲ اﻟﺸﺮوط اﻟﻤﻨﺎﺳﺒﺔ ﻣﻦ اﺟﻞ ﻣﻌﺮﻓﺔ ازﻣﻨﺔ C17 اﻻﺣﺘﻔﺎظ ﻟﮭﺬه اﻟﻤﺮﻛﺒﺎت و ذﻟﻚ ﻟﺘﻮظﯿﻔﮭﺎ ﻓﻲ ﻋﻼﻗﺔ "ﻛﻮﻓﺎﺗﺲ" ﻗﺼﺪ اﻟﺘﺤﻠﯿﻞ اﻟﻜﯿﻔﻲ ﻟﻠﻤﺮﻛﺒﺎت اﻟﺘﻲ ﺗﺘﻮاﺟﺪ ازﻣﻨﺘﮭﺎ ﻓﻲ ﺗﻠﻚ اﻟﻤﺠﺎﻻت . As you know, Gas Chromatography equipped with flame ionization detector (GC/FID) has the ability to perform quantitative measurements, and Gas Chromatography equipped with a Mass spectrometer (GC/MS) has the ability to perform qualitative analysis. In this work we provided a DATABASE for the Gas Chromatograph with flame ionization detector to enable it to perform qualitative analysis along with quantitation. A mixture of complex volatile compounds was used to evaluate and compare different linear velocities of the carrier gas (N2) and different temperature programs of column (DB-5) to determine the parameters used to optimize the separation. After, a series of saturated aliphatic n-Alkanes (C14 – C17) was injected into the gas chromatograph in the optimized operating conditions to determine their specific retention times and to apply in Kovat’s equation and evaluate the quality of unknown compounds situated in that field of retention times.